Detection of undescribed ostreid herpesvirus 1 (OsHV-1) specimens from Pacific oyster, Crassostrea gigas - Martenot, Claire; Lethuillier, Ophélie; Fourour, Sarah; Oden, Elise; Trancart, Suzanne; Travaillé, Emmanuelle; Houssin, Maryline (Journal of Invertebrate Pathology, 2015)
International audience The ostreid herpesvirus 1 (OsHV-1) and variants were implicated in mass mortality affecting the young Pacific cupped oysters, Crassostrea gigas, in European countries and those around the world. From 2008 onwards, oyster mortality had greatly increased on the French coast and was associated with the detection of a new OsHV-1 variant, entitled OsHV-1 μVar. The OsHV-1 μVar is predominant in oysters; however, other OsHV-1 variants have been detected in samples collected during mortality periods or collected out of mortality periods in France, Ireland, Spain, Portugal, Italy, Mexico, United States, South Korea, Australia, and New Zealand. A retrospective study conducted on 1047 OsHV-1 specimens sampled mainly in France between 2009 and 2012, revealed 17 undescribed OsHV-1 variants found in 65 oyster samples. These specimens presented point mutations situated downstream and upstream from the microsatellite area in the C region (ORF 4/5) which were different from the OsHV-1 reference and the OsHV-1 μVar. In the present work, investigation was performed to further characterize these OsHV-1 specimens by sequencing two habitually targeted regions to study genetic polymorphism of the virus: ORF 41/42 and ORF 35-38. An OsHV-1 variant detected in six oyster samples, contained a nucleotide substitution in the C region which impacted the amino acid sequence and might modify the function of the unknown protein encoding by ORF 4. For the ORF 41/42 region, only two specimens presented a synonymous mutation in comparison with the OsHV-1 μVar. All specimens contained the same deletion with the OsHV-1 μVar in ORF 35-38. Then, a phylogenetic analysis based on the C region was performed to investigate the distribution of undescribed specimens among 21 OsHV-1 DNA sequences notified in GenBank and collected from different countries (France, Japan, New Zealand, China, Ireland, and United States) between 1995 and 2012. All analyzed samples and the OsHV-1 μVar were placed in the same group, excepted for a Japan ...